INVENTORY OF KENYAH LEPO TAU SEGMENTAL SOUNDS - Asih, Yuni Utami (OKARA: Jurnal Bahasa dan Sastra, 2017)
Studies on the phonological description of Kenyah language are very limited. Initiated by Lees, she found 24 phonemes of Lepo Tau, one of Kenyah language branches are briefly explained on her article. Listing 18 consonants and 6 vowels, this article provides a preliminary analysis of the sound system of Lepo Tau. To a certain extent, Rufinus similarly states the same number of phonemes of the language. A study by Soriente in 2003 provides some more descriptions of the phonology of Kenyah language. It states that Lepo Tau language has 23 phonemes, 17 consonants and 6 vowels. Some of the result register 18 underlying forms of consonants in KLT which are phonetically realized into 23 representations of consonant. List of vowel shows 8 representations generated from 5 underlying forms of vowel. The descriptions of their representation include the nature of their 13 distinctive features.